ANALISIS SALURAN PEMASARAN BERAS ORGANIK DI DESA SUMBER SUKO KECAMATAN BELITANG KABUPATEN OGAN KOMERING ULU TIMUR (JASEP, 2019)
Sumbersuko village is one of the villages in the Belitang sub-district of east Oku District South Sumatera Province. This reseacrh was conducted to determine marketing channel of the organic rice in Sumber Suko Village Belitang Sub-District, East Ogan Komering Regency South Sumatera Province. This research was conducted in Sumber Suko Village, Belitang District, East Ogan Komering Ulu Regency, August to September 2018.This method used is case study method. The sampling in this study used the census method, based on data from the Agriculture Service of East Ogan Komering Ulu Regency, the number of organic rice farmers in Belitang Sub-District, Sumber Suko Village which is 40 people. for further sampling at middleman, merchant and consumers used snowball sampling. Processing and analysis of data in this research was carried out by desriptive. The results showed that there were 6 channels of organic rice marketing in Sumber Suko Village, namely: Channel 1 (Farmers – Joint Farmer Group - consumers), channel 2 (Farmers - Joint Farmer Group - retail - consumers), channel 3 (Farmers - middlemen - rice factory - distributors - retailers - consumers), channels 4 (Farmers - middlemen - rice factory - retailers - consumers), channels 5 (Farmers - middlemen – rice factories – retail - consumers) and channels 6 (Farmers - rice factories - distributors - retailers - consumers).